2016
DOI: 10.1080/08941939.2016.1230246
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Minimally Invasive Surgery in the Treatment of Lung Metastases

Abstract: Thoracoscopic surgery is a safe and efficacious procedure, with a five-year overall survival that is equivalent to open surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…He was able to show that the VATS group suffered from significantly less postoperative pain, had shorter in hospital treatment and a better compliance with regard to adjuvant treatment. These observations were later confirmed by other authors (12,13).…”
Section: Introductionsupporting
confidence: 85%
“…He was able to show that the VATS group suffered from significantly less postoperative pain, had shorter in hospital treatment and a better compliance with regard to adjuvant treatment. These observations were later confirmed by other authors (12,13).…”
Section: Introductionsupporting
confidence: 85%
“…Mutsaerts et al (12) reported similar survival in patients with solitary peripherally located metastasis comparing thoracoscopic and thoracoscopic followed by confirmatory thoracotomy approach. Similar results were demonstrated by other studies (13). Dong et al in a metaanalysis, including 6 retrospective studies showed that VATS resection has 1, 3, and 5-year survival rates and the 1-year disease-free survival rate which are almost equivalent to those of thoracotomy.…”
supporting
confidence: 89%
“…The authors concluded that, in selected patients, VATS is equally effective and less invasive than open surgery (39). This opinion is supported by other studies (40,41).…”
Section: Operative Techniquementioning
confidence: 54%